Aging successfully: possible in principle? Possible for all? Desirable for all? - Wahl, Hans-Werner (Integrative psychological and behavioral science, 2020)
The human lifespan is constantly increasing across the world. Therefore, the question whether aging can take a “successful” route likely never has been as up-to-date as today. Still, gerontology continues to struggle with the concept of successful aging. In part I of this work, I outline six models of successful aging currently most discussed in aging science. Next, I compare the models according to four indicator domains: Psychologically oriented, socially oriented, bio-physical functioning oriented, and other. In part II, I address three key questions related to successful aging: Is successful aging possible in principle? Is it possible for all? Is it desirable for all? Regarding the first question, the conclusion based on empirical data is that across all models except the biological model aging successfully is possible in principle. Hence, I answer this question with a “YES, BUT.” Successful aging at the bio-level so far seems very limited. In terms of question 2, expecting largely increasing portions of older adults fulfilling various of the so far established criteria of aging successfully in the future seem overly optimistic. Hence, I answer this question with “NO.” For question 3, I critique the at first glance obvious persuasiveness of successful aging as a generally to be achieved end state. For example, it may be that norms of successful aging undermine old age’s cultural richness in the future. Hence, I answer this question with “NOT SURE.”
Gesehen am 11.11.2021